Analisis Tata Kelolah Dana Desa dalam Pemberdayaan Masyarakat - Petrus Peleng Roreng; Adiel Kemal Pratama (Jurnal Buana Akuntansi, 2019)
This research aims to understand the impact of village funds allocation in people empowerment in Bombonglambe village, Mamasa regency. This research included type of qualitative descriptive research, using primary and secondary data collected by using interviews, documentation and observation. In this research, the authors analyzing the data by collecting, reducing, and presenting the data to find the conclusion. In this research, founded that people empowerment has not been fully implemented yet in Bombonglambe village. Keywords: village funds allocation, people empowerment